Child Poverty in Middle-Income Countries - Emily Nell; Martin Evans; Janet Gornick (Luxembourg Income Study (LIS), 2016)
This paper aims to better understand the income factors that influenced child poverty rates across a group of four diverse middle-income countries in 2010. We use data from LIS to analyze child poverty using harmonized measures of income in Russia, Mexico, South Africa, and Colombia. The paper addresses three main questions: First, how poor were children relative to other age groups in each country? Second, what income sources, including support from families and state transfers, protected children from higher rates of child poverty? For this question, we disaggregated incomes to identify tax and transfer profiles and their gross effect on poverty risk. Third, how did this look across a group of middle-income countries?
Keywords: 330